1981
DOI: 10.1111/j.1523-536x.1981.tb01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Reproduction in Women in Western Australia — A Review

Abstract: Beginning with a historical account of advice to breastfeeding mothers, the authors review recent changes in the incidence of breastfeeding in Perth, and studies of milk production, constituents of various milks, management of breastfeeding and weaning, and circadian and menstrual cycle variation in breastmilk. The effects of contaminants, the seasons, and pregnancy are also discussed. (Birth Fam J8:4, Winter 1981)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…It is clear that a large proportion of the women currently giving birth know about the value of breast-feeding and intend to nurse their babies. The present study indicates that intentions regarding duration are modest, especially in view of recommendations to breast-feed for 6 months and longer (Barness, 1981;Fomon et ah, 1979) and the fact that it is health-promoting for the infant (Ahn & MacLean, 1980) and that it is possible for the mother (Hartmann et al, 1981).…”
Section: Intentionsmentioning
confidence: 73%
“…It is clear that a large proportion of the women currently giving birth know about the value of breast-feeding and intend to nurse their babies. The present study indicates that intentions regarding duration are modest, especially in view of recommendations to breast-feed for 6 months and longer (Barness, 1981;Fomon et ah, 1979) and the fact that it is health-promoting for the infant (Ahn & MacLean, 1980) and that it is possible for the mother (Hartmann et al, 1981).…”
Section: Intentionsmentioning
confidence: 73%
“…A small‐scale, prospective study undertaken in a semi nomadic pastoral population in northern Tanzania showed that mothers often stated an intention to introduce adult staple foods and terminate breastfeeding at the end of the long rains (22). A study in Western Australia showed that seasonal conditions could have a significant effect in the level of milk production but the reasons were not fully understood (23). Because of the geographical location, Xinjiang has four very different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, raising twins to maturity requires more maternal investment (e.g. the production of around twice as much milk during the first 9 months of lactation 44 ), which may extend the duration of lactational amenorrhoea and delay the next reproduction. On the other hand, the higher mortality of twin offspring 1 , 5 , 7 , 16 18 , 45 may lead to shorter interbirth intervals.…”
Section: Resultsmentioning
confidence: 99%